2021
DOI: 10.1007/s11947-020-02574-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Free and Encapsulated Olive Leaf Phenolic Extract on the Storage Stability of Single and Double Emulsion Salad Dressings

Abstract: Valorization of wastes has become an unavoidable goal in the olive oil industry. A possible approach is the recovery of leaf phenolic compounds, which have a great interest for food industries, due to their antioxidant and antimicrobial activities. Thus, this study aims at comparing the effects of encapsulated (e-OLE) and free olive leaf extract (f-OLE) on storage stability of salad dressings prepared as single and double emulsion systems. Creaming, rheological properties, double emulsion yield, pH, total phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The K values of the OPE–RSGNP and OPE–CSGNP were higher than RSGNP and CSGNP mayonnaise samples, respectively, and differences were found to be statistically significant ( p < 0.05). A similar result was reported . In nature, plant polyphenols are often closely associated with polysaccharides as they both contain large amounts of hydrophilic groups and hydrophobic groups, so they can be complexed or cross-linked with polysaccharides. Due to the polysaccharide composition of dried olive pomace, pomace can be a potential source for gelling pectic material .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The K values of the OPE–RSGNP and OPE–CSGNP were higher than RSGNP and CSGNP mayonnaise samples, respectively, and differences were found to be statistically significant ( p < 0.05). A similar result was reported . In nature, plant polyphenols are often closely associated with polysaccharides as they both contain large amounts of hydrophilic groups and hydrophobic groups, so they can be complexed or cross-linked with polysaccharides. Due to the polysaccharide composition of dried olive pomace, pomace can be a potential source for gelling pectic material .…”
Section: Resultssupporting
confidence: 69%
“…A similar result was reported. 37 In nature, plant polyphenols are often closely associated with polysaccharides as they both contain large amounts of hydrophilic groups and hydrophobic groups, so they can be complexed or cross-linked with polysaccharides. 38 40 Due to the polysaccharide composition of dried olive pomace, pomace can be a potential source for gelling pectic material.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced-fat can be achieved in W 1 /O/W 2 because of the inner aqueous phase incorporated within the middle oil phase (Paximada et al, 2021;Saffarionpour and Diosady, 2021). (Jolayemi et al, 2021)Besides, DE can encapsulate both hydrophilic and lipophilic carriers simultaneously within a single carrier. Research done by Harimurti et al (2021) showed PGPR and Tween 20-stabilized DE had encapsulated both hydrophobic temulawak extract and hydrophilic red dragon fruit extract which impart higher antioxidant properties observed by the one-tenth lower IC 50 than unencapsulated extract.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are well-known, highly effective antioxidants that possess various health benefits, such as the prevention of cancer, inflammation, diabetes, and cardiovascular diseases [ 4 , 5 ]. They exist in a wide range of plants in nature, and are a well-known target for by-product or food-waste valorization, such as grape seeds [ 6 ], spent coffee grounds [ 7 ], carob pulp [ 8 ] and olive leaves [ 9 ]. Due to their sensitivity to light, heat, oxidation, and certain pH values, the encapsulation of polyphenols has been carried out using several technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst them, water-in-oil-in-water (W 1 /O/W 2 ) emulsions are a promising strategy based on their high encapsulation efficiency, chemical stability and increased bio-accessibility upon controlled release [ 4 , 10 , 11 , 12 ]. The incorporation of polyphenols encapsulated in W 1 /O/W 2 emulsions into several food matrices, for instance, yoghurt [ 10 , 13 ], salad dressing [ 9 ], and meat products [ 14 ], have been recently reported in the literature.…”
Section: Introductionmentioning
confidence: 99%